KRITIK SOSIAL DALAM RUANG PUBLIK: STUDI KASUS TAYANGAN ACARA LAPOR PAK! DI TRANS 7 - Abdul Syakur, Hilmy (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
Mass media which initially provided various kinds of information now also play a role as a public sphere to provide criticism, ideas and concepts. One of them is the Lapor Pak! broadcast owned by the mass media Trans 7. Using Zulkifli Hasan roasting episode. The focus of this study: 1) To find out how the Lapor Pak! Trans 7 episode